APPLICATION OF CROPPING ACTIVITIES TOWARDS SCIENCE KNOWLEDGE OF CHILDREN AGED 5-6 YEARS IN TK IT NADA ASHOBAH - Haniya; Ruqoyyah Fitri (Adisam Publisher, 2024)
This introduction discusses the importance of early childhood education in shaping the growth and development of children, especially in cognitive development. The golden period of childhood, particularly at the age of 5-6 years old, is a crucial time in forming personality and understanding of the surrounding environment. One important aspect to develop during this period is cognition, which involves various abilities such as attention, memory, and logical thinking. Science learning activities, especially through gardening methods, are an interesting approach to enhance the scientific understanding of young children. Through these activities, children can learn in a fun and contextual way while developing science process skills and understanding of the environment. The subjects of this research are 3 children aged 5-6 years old. The research method used is qualitative, involving observation, interviews, and literature studies to gain a deep understanding of the influence of gardening activities on the scientific knowledge of young children. Data analysis techniques use data reduction, data presentation, and drawing conclusions. The results show that gardening activities have a significant impact on the development of children, both in terms of knowledge, skills, and attitudes. This indicates the importance of introducing scientific concepts to young children through fun and relevant approaches to their daily lives.